Serious sports injuries of judoka in Japan including ACL injury, head injury, and unconsciousness via shime-waza - Kamiya, N.; Yoshida, I.; Kazuhisa, O. (The Arts and Sciences of Judo, 2023)
The purpose of this study was to investigate three serious conditions, ACL injury, head injury, and unconsciousness by shime-waza in collegiate judoka. In total 518 athletes (286 male and 232 female) were recruited with an average age of 19.7±1.3 years, more than 10 years of judo experience (12.5±2.8 year, and relatively high judo grade (2.0±0.52). ACL injury was seen in 70 athletes (average 13.7%), in which 48 athletes (71.6%) received ACL reconstruction surgery. After athletes returned to competition, 45.0% recognised their performance as equal to pre-injury levels. The remainder had some concems regarding physical functios (i.e. reductions in leg muscle power, core stability, knee range of motion, knee pain, etc). Out of 475 athletes, 148 had experience of head injuries (31.2%), in which concussion was the most frequent (83.1%). The judo grade (dan) at the time Of head injury (1.24±0.71) was significantly Iower than that of the current grade (2.04±0.51). After head injury, 45.2% of athletes returned to judo practice within the next day. The incidence of unconsciousness from shime-waza (59.1%) was similar to that of providing unconsciousness by shime-waza (57.4%). The judo grade (dan) at the time of unconsciousness by shime-waza (0.88±0.60) was significantly Iower than that ofthe current grade (2.02±0.53). There was a significant correlation between the experience of head injury and unconsciousness by shime-waza. This study demonstrates the incidence and factors of serious injuries in judo and provides milestones to improve the environment ofjudoka.